EFFECT OF WORK COMPENSATION AND DISCIPLINE OF EMPLOYEE PERFORMANCE IN PT. INDAKO TRADING COY - Idawati Purba (Sean Institute, 2022)
The purpose of this study is to determine whether compensation and work discipline affect the performance of employees at PT. Indo Trading Coy (Krakatau Branch, Medan). Employee performance is influenced by several factors, one of which is compensation. Salary, Bonuses, Insurance, Office Facilities and Allowances are factors that trigger employees to improve their performance. Other factors that affect employee performance are work discipline which includes quality of work, quantity of work and the determination of work completion time. Work compensation and discipline is the most important factor to improve employee performance in a company. Collection of data that has been obtained is then analyzed using quantitative descriptive research. The population in this study is the number of employees working at PT.Indako Trading Coy (Krakatau branch, Medan) as many as 80 people. The number of samples used in this study were 80 people. This research uses t test, F test, determination test and multiple linear regression analysis. The results showed that the compensation variable partially influenced the performance of employees at PT. Indako Trading Coy. The results showed that the variable work discipline partially influenced the performance of employees at PT. Indako Trading Coy. The results showed that there was a positive and significant effect between compensation and work discipline on the performance of employees at PT Indako Trading Coy, this has been proven based on the F test results obtained at a calculated F value of 308.284 with a significance value of 0.000. so the significance of F <5% (0,000 <0.05) means that the variable compensation and work discipline simultaneously affect the purchase interest. The conclusion in this study is that compensation and work discipline affect the performance of employees at PT. Indako Trading Coy (Krakatau branch, Medan).